A Quality control sudy on Australasia Cylinder Corporation - Clemente, Daniel Ricardo; Gaffud, Walter Ryan; Ng, May Antoinette; Santos, Vina Morena (College of Engineering, 1997)
The group performed a quality control study on Australasia Cylinder Corporation, a company of the F. Jacinto group of companies specializing in the manufacturing of liquid gas cylinders. Through plant visits and course coverage, the group aimed to apply the techniques of quality control to the production of LPG cylinders in order to come up with recommendations involving their quality systems. The group found out that the company, despite its large size, had never applied control charting or acceptance sampling techniques in the monitoring of their cylinders. As part of the recommendations, the group provided guidelines in implementing a system of control charting and acceptance sampling. The company's existing forms were revised so as to include the relevant information. Other problems related to work study were encountered. Since this is beyond the scope of the study, only a general outline to improve the system was made.